Management 4.0: Concept, applications and advancements - Abid Haleem; Mohd Javaid; Ravi Pratap Singh; Rajiv Suman; Shahbaz Khan (Sustainable Operations and Computers, 2023)
Management 4.0 assists businesses in evolving, surviving and performing in the competitive and dynamic world. This fourth revolution uses advanced technologies like Artificial Intelligence (AI), Virtual Reality (VR), Internet of Things (IoT), Robotics, Holography, Additive Manufacturing etc., for the proper management systems. These technologies facilitate working personnel and make it more appealing to complete their duties efficiently and accurately. The main aim of this paper is to understand the concept of Management 4.0, its technologies and applications for proper management systems. As Management 4.0 enhances process control, the chance of human error is reduced, leading to increased efficiency. It enables rapid and intelligent decision-making, reduces costs, accelerates growth, and raises profitability. Management 4.0 technologies and advanced data analytics are helpful to make smart supply chain management well suited to fulfil industry 4.0. Thus, to overcome various obstacles and effectively deploy Management 4.0 technologies in manufacturing industries, top management must establish a clear asset performance management plan with the help of process engineers familiar with industrial system failure occurrences and what operators need to improve. Management 4.0 involves advanced technologies, system connectivity, data collection & analysis at the organisation level. Management 4.0 is expected to be a critical component in the long-term survival of any business, either manufacturing or service-providing organisations. This paper explores the development of Management 4.0 and its dimensions and transformations through Management 4.0 perspectives. Finally, the significant role of Management 4.0 for appropriate private management system in manufacturing industries are identified. Organisations require a system that seamlessly meets the company's expectations, consumers, investors, and other stakeholders to remain competitive, and Management 4.0 will enable this. Many businesses strive to integrate technologies and upskill their personnel to adapt to the new job duties and attract more workers with the necessary abilities.